2017
DOI: 10.1007/s11934-017-0651-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Margins in Nephron-Sparing Surgery for Renal Cell Carcinoma

Abstract: The oncologic impact of positive surgical margins after nephron-sparing surgery is controversial. Herein, we discuss current data surrounding surgical margins in the operative management of renal cell carcinoma. The prevalence, risk factors, outcomes, and subsequent management of positive surgical margins will be reviewed. Literature suggests that the prevalence of positive surgical margins following kidney surgery varies by practice setting, tumor characteristics, and operation type. For patients undergoing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 70 publications
1
25
0
4
Order By: Relevance
“…Hospital volume categories were determined according to the following criteria: very low volume, 1-7 cases (n = 3 693); low volume, 8-14 cases (n = 3 719); medium volume, 15-23 cases (n = 3 833); high volume, 24-43 cases (n = 3 649); and very high volume, ≥44 cases (3 830). The median (interquartile range) hospital volume increased from 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Baseline characteristics of the cohort are summarized in Table 1. The unadjusted outcome comparison across the strata of hospital volume is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hospital volume categories were determined according to the following criteria: very low volume, 1-7 cases (n = 3 693); low volume, 8-14 cases (n = 3 719); medium volume, 15-23 cases (n = 3 833); high volume, 24-43 cases (n = 3 649); and very high volume, ≥44 cases (3 830). The median (interquartile range) hospital volume increased from 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Baseline characteristics of the cohort are summarized in Table 1. The unadjusted outcome comparison across the strata of hospital volume is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nephron-sparing surgery has an advantage because of the possibility of histological verification and evaluation of surgical margins. If these margins are negative for a tumorous process, then the treatment is considered radical [ 14 ]. The disadvantages of surgical treatment include an operation wound in the lumbar region, which is often painful and requires general anesthesia and may lead to further complications such as seroma, urinoma, inflammation, or vascular impairment (pseudoaneurysm) with a high risk of serious bleeding [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 In PN, the incidence of positive surgical margins (PSMs) in patients with small renal masses varies from 0.1 to 7% and for advanced RCC patients, from 18 to 32%. 2,3 Although the impact of PSM on long-term survival in RCC remains controversial, 4 large observational studies have shown that PSMs are significantly associated with higher rates of local recurrence and worse overall survival independent of other predictors. [5][6][7] Despite the importance of surgical margin assessment, only 69% of surgeons performing open and 58% performing laparoscopic PN report using intraoperative frozen sections (IFSs).…”
Section: Introductionmentioning
confidence: 99%